Li induced enhancement in c-axis orientation and its effect on structural, optical, and electrical properties of ZnO thin films - Ali, Dilawar; Butt, M. Z.; Arif, Bilal; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2017)
Un-doped and Li-doped ZnO thin films with high c-texture have been deposited on glass substrate using sol-gel spin coating method. The effect of Li dopant in concentration range 1-5 at.% on the structural, optical, morphological, and electrical properties of ZnO thin films were analyzed using x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV-VIS spectrophotometer, field emission scanning electron microscopy (FESEM), and two point probe method, respectively. XRD analysis reveals that all thin films possess hexagonal wurtzite structure and (0 0 2) preferred orientation. X-ray diffraction intensity and crystallite size appertaining to (0 0 2) plane increases with the increase in Li concentration. FESEM micrographs shows that morphology of all thin films consist of spherical and non-spherical shaped grains. Surface roughness of the films decreases on increasing Li dopant concentration. Average transmittance in visible region is 90.6 +/- 0.5 % for all Li-doped ZnO thin films. Blue shift, i.e. widening of optical band gap (Eg) has been observed on doping with Li. Urbach energy (Eu) was found to decrease on Li incorporation. Both Eg and Eu correlate well with variation in c-texture and crystallite size. The average refractive index of ZnO thin films in the visible region is decreased on doping with Li. Electrical conductivity of ZnO thin films is enhanced on increase in Li dopant concentration. The improvement in electrical conductivity also correlates well with increase in c-texture and crystallite size. FTIR spectra portray characteristic absorption bands centered at 901, 760, 602, and 568 cm(-1) pertaining to metal-oxygen bonds.
Keywords: ZnO thin films; sol-gel; x-ray diffraction; band gap energy; refractive index; electrical conductivity; FTIR analysis